TNFRSF11A‐Associated Dysosteosclerosis: A Report of the Second Case and Characterization of the Phenotypic Spectrum. (5th August 2019) - Xue, Jing‐yi; Wang, Zheng; Shinagawa, Satoshi; Ohashi, Hirofumi; Otomo, Nao; Elcioglu, Nursel H; Nakashima, Tomoki; Nishimura, Gen; Ikegawa, Shiro; Guo, Long
ABSTRACT: Dysosteosclerosis (DOS) is a distinct form of sclerosing bone disease characterized by irregular osteosclerosis and platyspondyly. DOS is genetically heterogeneous; however, only five cases with SLC29A3 mutations and a single case with a splice‐site mutation of TNFRSF11A have been reported, and TNFRSF11A is also a causal gene for osteopetrosis, autosomal recessive 7 (OP‐AR7). Thus, the causal genes of DOS and their genotype‐phenotype associations remain unclear. In this study, we examined a Japanese patient with DOS and found a novel variant in TNFRSF11A . The homozygous variant was a G to T transversion at the first nucleotide of exon 9 (c.784G>T). Although the variant was predicted to cause a stop codon mutation (p.E262*), in silico evaluation of the exonic splicing elements followed by RT‐PCR for the patient‐derived cells showed that it caused aberrant splicing due to the change in the exonic splicing element and produced two types of aberrant transcripts: One caused a premature stop codon (p.E262Vfs*17) leading to nonsense mutation‐mediated mRNA decay; the other produced a protein with interstitial deletion (p.E262_Q279del). The effects of the mutation on five splicing isoforms of TNFRSF11A were different from those in OP‐AR7, but comparable with those in the first DOS with the TNFRSF11A mutation. Thus, we identified the second case of DOS caused by the TNFRSF11A splice‐site mutation and confirmed the novel disease entity. © 2019 American Society for Bone and Mineral Research.